Which Shape Characteristics of the Intermolecular Interaction of Liquid Water Determine Its Compressibility? - Yasutomi, Makoto (Frontiers in Physics, 2016)
We consider a fluid of spherical particles with a pair potential given by a hard core repulsion and a tail, and show that the isothermal compressibility of liquid water is determined by the degree of steepness of the soft repulsion near the hard-core contact. This helps us understand the thermodynamic mechanism that causes the compressibility anomaly of liquid water.